Novel Bis Maleimide Derivatives Containing Azo Group: Synthesis, Corrosion Inhibition, and Theoretical Study - Hawraa Kareem Dhaef; Rafid Humaidan Al-Asadi; Ashwaq Abood Shenta; Mohammed Khalaf Mohammed (Universitas Gadjah Mada, 2021)
Novel derivatives of heterocyclic azo compounds have been synthesized through a free catalyst reaction. The structures of the synthesized compounds were confirmed by using different techniques such as 1H-NMR, 13C-NMR, and mass spectroscopy. The prepared derivatives were evaluated as corrosion inhibitors for mild steel after the inhibitory performance toward mild steel in 0.1 M HCl solution. The prepared derivatives, i.e. (1,1'-(((1E,1'E)-1,4-Phenylenebis(diazene-2,1-diyl))bis(4-methyl-3,1-phenylene))bis(1H-pyrrole-2, 5-dione)) 1 and (1,1'-(((1Z,1'Z)-(Oxybis(4,1-phenylene))bis(diazene-2,1-diyl)) bis(4-methyl-3,1-phenylene))bis(1H-pyrrole-2,5-dione)) 2 showed inhibition efficiency 89.22% and 91.30%, respectively at concentration 1 × 10–3 M. The isotherm adsorptions of these derivatives were found to obey Langmuir model. Furthermore, Density functional theory was used for theoretical estimation of the HOMO, LUMO, and other chemical quantum parameters. The results indicated that the synthesized derivatives displayed a corrosive inhibitory property in which derivative 2 was more effective than derivative 1. In addition, the theoretical results were in agreement with the experimental data.